Document Delivery-Past, Present and Future - Sathyanarayana, N.V. (DESIDOC Journal of Library & Information Technology, 2002)
Source: DESIDOC Bulletin of Information Technology :15(1) ; 1995 ; pp.12-16 Abstract : The origins of document delivery, as the term came to be known, is from an.Inter-library loan and photocopying service for journal articles, offered by libraries largely free of cost. For long, it remained a passive and co-operative service spear-headed by library networks as part of their resource sharing plans. British Library Document Supply Centre (BLDSC), UK was the only organisation which extended the service from journal articles to conference papers and other documents such as theses, dissertations and reports. The service evolved and grew in demand with the gradual increase in the usage of bibliographic databases. For the first time,Current Contents published by the Institute of Scientific lnformation (ISI), USA expanded the scope of document delivery outside the library networks by providing a means for direct contact between the user and the author or publisher. http://dx.doi.org/10.14429/dbit.15.1.3173